Techno Economic Evaluation and Feasibility Analysis of a Hybrid Net Zero Energy Building in Pakistan: A Case Study of Hospital - Arif, Saba; Taweekun, Juntakan; Ali, Hafiz Muhammad; Theppaya, Thanansak (Frontiers in Energy Research, 2021)
The current study is an economic evaluation and feasibility study of hybrid microgrid Net Zero Energy Buildings in Pakistan. A Net Zero Energy approach is proposed for a two-story hospital building situated in Taxila, Pakistan. Consequently, to design a hybrid Net Zero Energy Building, the solar radiation potential of the subject location and electricity usage of the hospital are estimated. The proposed hybrid microgrid Net Zero Energy Building comprises photovoltaic modules and converters. However, the thermal load is computed as a grid-connected hybrid system. Economic evaluation is performed by using economic indicators of the net present cost and the payback period. Also, initial and operational costs are determined, to determine the profitability of the project. Results show that the analysis is a cost-effective approach and has a payback period of 2.53y. Additionally, the per-unit cost of electricity is reduced to 0.12 USD/kWh. Moreover, the energy produced by a hybrid system is 10.24% more economical than that of the pre-working grid system. Results explain the reduction in the cost of energy and profit margin in electricity generation and the increase in electricity production and feasibility of hybrid Net Zero Energy Buildings in Pakistan. Research will help to develop an approach toward an IEA task 47 in Pakistan with the possible development of simulation-based installations of Net Zero Energy Buildings in the health sector in Pakistan.